Abdominal fat depots, insulin resistance, and incident diabetes mellitus in women with and without HIV infection. (31st July 2018) - Glesby, Marshall J.; Hanna, David B.; Hoover, Donald R.; Shi, Qiuhu; Yin, Michael T.; Tien, Phyllis C.; Cohen, Mardge; Anastos, Kathryn; Sharma, Anjali
Abstract : Objective: The aim of this study was to determine the associations between visceral adipose tissue (VAT) and abdominal subcutaneous adipose tissue (SAT) mass with homeostatic model assessment-insulin resistance (HOMA-IR) and incidence of diabetes mellitus in women with and without HIV infection. Design: Cross-sectional design for associations between abdominal fat and HOMA-IR; longitudinal design for associations between abdominal fat and incident diabetes. Methods: We assessed associations between dual X-ray absorptiometry scan-derived VAT and SAT with HOMA-IR in a subsample from the Women's Interagency HIV Study ( n  = 226 with and n  = 100 without HIV) using linear regression. We evaluated associations of VAT, SAT and HOMA-IR with incident diabetes mellitus using Cox proportional hazards models. Results: VAT mass was positively associated with log HOMA-IR in fully adjusted linear regression models stratified by HIV serostatus, including adjustment for SAT. During median follow-up of 10.6 years, incidence of diabetes was 1.63 [95% confidence interval (95% CI) 1.15–2.31] and 1.32 [95% CI 0.77–2.28] cases per 100 person-years in women with and without HIV ( P  = 0.52). In a fully adjusted model, baseline VAT (hazard ratio 2.64 per kg; 95% CI 1.14–6.12; P  = 0.023) and SAT (hazard ratio 1.34 per kg; 95% CI 0.73–2.45; P  = 0.35) were associated with incident diabetes, but the latter was not statistically significant. Conclusion: VAT mass was independently associated with HOMA-IR in women with and without HIV and was independently associated with future development of diabetes. Abstract : Supplemental Digital Content is available in the text